Women Exploitation in Prostitution Business - Pratama, Yoga Nanda (Universitas Negeri Semarang, 2019)
Women are respected and worth to be respected. Although women often get unfair treatment and often underestimated and even in some countries women are deemed unfit to live and worse, they kill babies of female or female sex. Until now women from different parts of the world are fighting for their rights and struggling to gain recognition and be well treated by the world. However, today there are still often found crimes involving women, one of which is a prostitution business that is very synonymous with the exploitation of women. Women who have struggled with difficulty still have to face the serious problems that still occur today. This journal will discuss more about the exploitation of women, ranging from factors, reasons and causes why there are women who are exploited by irresponsible people